DPPH FREE RADICAL SCAVENGING ACTIVITY OF LEMPUYANG WANGI LEAVES (ZINGIBER AROMATICUM. VAL) EXTRACTS AND FRACTIONS - Cheleng, Nisreen; Hanwar, Dedi (Prosiding University Research Colloquium, 2024)
Zingiber aromaticum has chemical compounds such as flavonoids, saponins and essential oils. This research aimed to know antioxidant activity and determine the total phenolic content in the leaves of Zingiber aromaticum. Extraction by maceration with ethanol and followed by fractionation of liquid-liquid separation method with ethanol solvent, n- hexane and ethyl acetate. The antioxidant activity of extracts and fractions determined by DPPH and total content of phenolic compounds determined by the Folin-Ciocalteu method. The results showed that the ethanol extract has IC50 value of 276.75 ppm, n-hexane fraction of 255.24 ppm, ethyl acetate fraction of 224.89 ppm, ethanol fraction of 420.39 ppm, and vitamin E of 6.488 ppm. Total phenolic content of the ethanol extract of 55.876 GAE, n-hexane fraction of 20.552 GAE, ethyl acetate fraction of 94.309 GAE, and ethanol fraction of 35.559 GAE. The correlation between antioxidant activity and total phenolic content was 46.31 % in the antioxidant activity of phenolic compounds discordant.